STRATEGI KESANTUNAN YANG TERCERMIN DARI KALIMAT BERPOLA ~TE MO II DAN ~NAKUTE MO II DALAM BAHASA JEPANG - , NAWIA YESI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study investigates politeness strategies depicted from ~te mo ii and ~nakute mo ii patterned sentence in Japanese. The sentence patterns used in this study are limited only for ~te mo ii and ~nakute mo ii patterns in Japanese. The limitation of the analysis is intended to more focused into the usage of ~te mo ii and ~nakute mo ii patterned sentence on speech aspects using pragmatic theory and politeness strategy. This research applies a correlation descriptive method, a research that is done solely on facts or phenomena that happen to the speakers, so that the results of the study is exposures as what it is based on the pragmatic theory applied. The results of this study show that from five strategies proposed by Brown and Levinson, there are only four strategies can be applied on ~te mo ii and ~nakute mo ii patterned sentence in Japanese. They are bald on record strategy, positive politeness strategy, negative politeness strategy, and off record strategy.